Study of Arabidopsis thaliana salt stress protection by beneficial bacteria - Bentria, Nour Elhorra; Berrabah, Fathi, Directeur de thèse (Laghouat : Université Amar Telidji - Département de biologie, 2024)
Salinity is one of the world's major issues affecting soil quality and agricultural productivity. Some plant growth-promoting bacteria that can thrive in regions with high salt concentrations (NaCl) biotic and abiotic stress have the ability to promote plant growth in salty environments. Arabidopsis thaliana is a model plants giving a precious help for understanding the plant sensibility and resistance to the salt stress. In this study we harvest A. thaliana sensibility to salt stress, we assess the role of the defense hormone salicylic acid (SA) in this response by the study of plant overexpression SA-degrading enzyme (NohG) or impaired in SA signaling (nrp1). Our results indicate that the NaCL at 100mM is sufficient to inhibit the growth of A. thaliana cultivated in vitro. Interestingly, 35S::NohG shows increase of the plant growth in absence of salt stress and increase of sensitivity to the NaCl. By contrast the mutant npr1 show similar behavior with the WT in absence or presence of NaCl. Four Medicago truncatula bacterial endophytes (M17, M50, S113 and S116) were tested for their ability to reduce the salt stress on A. thaliana. The strain S116 increase the resistance and the growth of A. thaliana in response to salt stress, wherase the other strain shows reduction of the impact of the NaCl on the plant growth. Inoculation of 35S::NohG and npr-1 with the studied strain reveals that the resistance mediated by the bacteria required correct SA synthesis and signaling. Finally comparative genomic analysis reveals the presence of shikimate kinase and salicylate esterase in M50 closest strain suggesting a potential manipulation of the SA pathway for the increase of A. thaliana resistance to the salt stress.